Saline waters and macroinvertebrates in subtropical Andean streams - González Achem, Ana Lucía (2015)
Salinity of rivers is an expression of the concentration of salts dissolved in the water body. Secondary salinization is the increase in salinity of a water body as a result of human activity. Salinity may restrict the species composition of aquatic biota to tolerant species. In this study we analyzed benthic communities and their relationship with physicochemical variables in natural pristine systems and impacted environments. We collected benthic community samples using a D-net and water samples for laboratory major ions analysis. We noted a critical limit of electrical conductivity above 800µS/cm breaking up taxa pools of benthic macroinvertebrates. We observed that taxonomic richness is a sensitive indicator to detect effects of secondary salinization. We hypothesized that the monsoonal precipitation regime of the studied region is an important driver of environmental conditions for the benthic fauna since it regulates the concentration of major ions. The evidence collected shows that seasonal rainfall may affect differentially the benthic communities of Andean streams, improving the equitability below 800µS/cm in saline sites while changing the community structure from equitable to one dominated by a certain taxa in less saline locations.